PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN PENGUASAAN KONSEP PESERTA DIDIK - Anton, Ebriani; Walukow, Auldry F.; triwiyono, triwiyono (Universitas Cenderawasih, 2024)
A study was conducted at SMP Negeri 2 Jayapura on how Student Teams Achievement Division (STAD) Cooperative Learning aims to determine the improvement and differences in students' mastery of concepts between the experimental class taught using the STAD cooperative learning model and the control class taught with conventional learning on the subject of vibrations and waves. The results showed that the exploratory class had a more significant level of idea dominance than the control class. In the control class, there were several obstacles encountered by students, such as lack of understanding due to abstract concepts, difficulty understanding the graphs or diagrams presented, lack of practical experience, more reliance on memorization and difficulty applying formulas, students were still passive, and difficulty connecting theory with real phenomena. While in the experimental class, the application of the STAD model made students more active in collaborating and conducting group discussions so that social skills were more developed and reduced stress and there was reinforcement through feedback so that students were more motivated. This quantitative research was conducted by applying the nonequivalent control group design model. The sample was class VIII A and VIII C of SMP Negeri 2 Jayapura. Learning by implementing the STAD cooperative model shows the development of students' ability to master concepts with an n-gain score of 0.75 in the group of students who have high concept mastery and 0.58 in the group of students who have low concept mastery. The application of the conventional model and the STAD cooperative model in both classes significantly increased all materials. The difference is indicated by a significance value of 0.05 of 0.000. Based on these results, it can be concluded that STAD type cooperative learning can improve students' understanding of vibration and wave materials.